Pengaruh Penggunaan Media Webtoon Pada Keterampilan Menulis Cerpen Siswa Kelas VII UPTD SMP Negeri 6 Pematang Siantar - Esna Bancin; Marlina A Tambunan; Immanuel D.B Silitonga (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2023)
This research aims to determine short story writing skills based on Webtoon of class VII UPTD students at SMP Negeri 6 Pematang Siantar. The type of research used is quantitative research. The purpose of this research is to see the influence of Webtoon on short story writing skills. The target of this research was class VII students of UPTD SMP Negeri 6 Pematang Siantar. The method used is quantitative One group Design with pretest Posttest. The results of this research indicate that there is a significant influence of the use of Webtoon on the short story writing skills of class VII students at SMP Negeri 6 Pematang Siantar. This is proven by the results of the tcount of 18.10 which is greater than the ttable of 1.670. So the alternative hypothesis is accepted, where there is an influence of using Webtoon on the writing skills of class VII UPTD students at SMP Negeri 6 Pematang Siantar.